Pemanfaatan Alam Sekitar sebagai Sumber Belajar Kontekstual dalam Pembelajaran IPAS di Sekolah Dasar - Monica Yesin; Herlina; Ma’ruf (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe the use of the surrounding environment as a contextual learning resource in natural and social sciences (IPAS) learning in elementary schools. A contextual approach is considered capable of bridging students' understanding of IPA concepts through direct experience and interaction with the surrounding environment. This study used a descriptive qualitative approach with teachers and fifth-grade elementary school students as subjects. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that utilizing the surrounding environment—such as school gardens, small rivers, parks, and social facilities—can increase learning interest, active involvement, and a deeper understanding of concepts. Activities such as direct observation, exploration, and field discussions make the learning process more meaningful. Thus, utilizing the surrounding environment as a contextual learning resource is effective in supporting active, real-life, and relevant IPA learning in students' lives.